The effect of brand extensions on product brand image - ARSLAN, FATMA MÜGE (My University, 2010)
Purpose: The purpose of this study is to investigate the effects of fit, familiarity, perceived quality and attitude towards the brand on product brand image after an extension and also to examine whether the product image of a brand is diluted as a result of brand extension. Design/methodology/approach: The model adopted for the study is based on that developed by Martinez and de Chernatony. A questionnaire consisting of seven constructs (general brand image, product brand image, quality, familiarity, fit, attitude, and demographic characteristics) was administered to 474 respondents. Convenience sampling and face-to-face survey methods were used. The brands and extensions used in the study were the same as in the Martinez and de Chernatony study. The difference between these two studies is that, while Martinez and de Chernatony have investigated the effects of brand extension on both general brand image and product brand image, in this study general brand image is examined only before the extensions in order to compare the two brands. The results of the pre-tests showed that Turkish consumers could not assess the effects of hypothetical extensions on the general brand image. Therefore, as for the effects of brand extensions, only the product brand image after the extension is investigated. Findings: The results show that brand extensions affect the product brand image negatively, whereas the fit between the parent and extension brands decreases the negative effect. The drop of image as a result of extension is greater when the perceived image and quality of the parent brand are higher. Perceived quality of the brand, consumers' brand familiarity, fit perceived by the consumer, consumers' attitudes towards the extension have a positive effect on the product brand image after the extension. Research limitations/implications: Owing to the sample size and sampling method, the study has its own limitations in terms of external validity. In addition, only two brands and two extensions were tested and the extensions used were hypothetical, which may lead to a lack of generalizability. Practical implications: The higher the image of a brand, the more the dilution that occurs, which means that companies should take caution when extending into different product categories. Originality/value: The study is one of the very few research efforts conducted in the Turkish market concerning brand extensions and the sample used in the research consists of consumers rather than students. © Emerald Group Publishing Limited.
Keywords: Brand awareness; Brand image; Consumer behaviour